1303. Characterization of Isavuconazole Serum Concentrations with Various Administration Routes in a Hospitalized Cohort. (31st December 2020) - Spivey, Justin; Wrenn, Rebekah; Liu, Beiyu; Maziarz, Eileen K; Maziarz, Eileen K; Kram, Bridgette
Abstract: Background: Patients with invasive fungal infections are often critically ill and immunosuppressed with multiple comorbidities that may impact drug absorption and exposure. This study sought to characterize isavuconazole serum concentrations (ISCs) in a cohort of real-world hospitalized patients when administered by intravenous solution (IV), enteral as intact capsules, or tube as opened capsule contents. Methods: This retrospective cohort analysis included all hospitalized patients who received isavuconazole as prophylaxis or treatment between September 2017 and September 2018 and had therapeutic drug monitoring performed. For patients receiving isavuconazole by tube, the capsules were opened and contents were diluted with 10-30 mL of sterile water. Administration was per package insert for intact capsules and IV solution. ISCs were obtained as part of routine care and were quantified by high-performance liquid chromatography. An appropriate trough was defined as within 4 hours of the next scheduled dose. Currently, there is a lack of correlation between isavuconazole exposure and efficacy or toxicity; thus, ISCs were compared between administration routes. Results: 93 ISCs were obtained during 65 encounters from 55 unique patients. The majority of patients were post-transplant (69.1%) and death occurred during 12 (18.5%) encounters. ISCs based on different characteristics of the cohort are shown in Table 1. All ISC assessments were detectable, median 2.3 mg/dL (Q1: 1.5 mg/dL, Q3: 3.3 mg/dL). Administration via tube achieved similar ISCs compared with IV therapy (1.6 mg/dL vs. 1.9 mg/dL, respectively). However, administration of intact capsules resulted in higher median ISCs, 3 mg/dL (Q1: 1.9 mg/dL, Q3: 4.1 mg/dL). All 14 patients with administration via tube were post-transplant, which was not shown to have a significant impact on ISCs (median, transplant 2.2 mg/dL vs. non-transplant 2.7 mg/dL). Table 1. Characterization of Isavuconazole Concentrations Conclusion: ISCs were detectable in all patients regardless of transplant status or location at the time of assessment. Administration of isavuconazole via an enteral feeding tube achieved comparable serum concentrations compared with FDA-approved routes of administration and may represent an important alternative for select patients. Disclosures: All Authors : No reported disclosures